The Influence of Procurement and Development Strategy on HR Productivity and Satisfaction - Madiistriyatno, Harries (Devotion : Journal of Research and Community Service, 2021)
The purpose of this paper is to describe the influence of the procurement and development function on the productivity and satisfaction of HR, as one of the tasks of the HR Management (Advanced) course. The purpose of this paper is to determine and examine the effect of the procurement function on HR productivity, HR satisfaction, HR productivity, HR satisfaction and development on HR productivity and satisfaction. This study uses a library research method that refers to resources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The result of this research is that the Procurement Function affects the Productivity of Human Resources. The Procurement Function has an effect on Human Resource Satisfaction. The Development Function affects the Productivity of Human Resources. The Development Function has an effect on Human Resource Satisfaction. The Procurement and Development Function affects the Productivity and Satisfaction of Human Resources.